2020
DOI: 10.3390/agronomy10020239
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Growth Performance of Super Rice under Water-Saving Irrigation Methods with Different Water-Controlled Thresholds in Different Growth Stages

Abstract: Many water-saving techniques have been developed for rice production in response to irrigation water scarcity. The selection of the water-saving methods and the optimum thresholds for obtaining maximum benefits of these regimes are largely site-specific depending mainly on soil type, soil texture, and the environment. A two-year (2017 and 2018) experiment was conducted to evaluate the response of the agronomic growth performance, yield, and water use of super rice varieties under different irrigation regimes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
5
8
0
Order By: Relevance
“…Other studies have postulated that more yield under AWD might be attributed to better grain-filling and increased root proliferation to take up more water and nutrients [74,77]. This is in agreement with [65], who reported up to 13% yield increase under watersaving irrigation treatments compared to flooding irrigation. Ref.…”
Section: Effect Of Water Management Nitrogen Levels and Their Interaction On Yield Characteristics Of Ricesupporting
confidence: 79%
See 2 more Smart Citations
“…Other studies have postulated that more yield under AWD might be attributed to better grain-filling and increased root proliferation to take up more water and nutrients [74,77]. This is in agreement with [65], who reported up to 13% yield increase under watersaving irrigation treatments compared to flooding irrigation. Ref.…”
Section: Effect Of Water Management Nitrogen Levels and Their Interaction On Yield Characteristics Of Ricesupporting
confidence: 79%
“…These results are in agreement with [63,64], who reported an increase of plant height under AWD water management and 90 kg N ha −1 nitrogen level. However, Zheng et al [65] reported contradicting results from China, showing that the final plant height was significantly higher under flooding irrigation than of that under water-saving irrigation treatments during both years of experiments.…”
Section: Effect Of Water Management and Nitrogen Levels On Plant Height And Number Of Tillersmentioning
confidence: 89%
See 1 more Smart Citation
“…The number of spikelets per panicle and the number of panicles per plant are determined well before flowering, but the fertility of spikelets, in particular functional pollen, is determined during the 10 days before and around flowering. Strategic irrigation did improve the number of spikelets per panicle (Table 5), in accordance with the data of [63], and averaged over both years increased spikelet fertility of all varieties, on average by 36%.…”
Section: Effects Of Planting Time Maturity Class and Strategic Irriga...supporting
confidence: 86%
“…Both of these parameters, the number of productive tillers and the 100 grain weight, affect the grain weight per plant. With more productive tillers and larger grains, the grain weight per plant increases [23]. As stated earlier, panicle formation is strongly influenced by nutrient availability, of which nitrogen is crucial [24].…”
Section: Resultsmentioning
confidence: 79%